Peran Skrining Indeks Massa Tubuh Dan Rasio Lingkar Pinggang-Pinggul Dalam Edukasi Pencegahan Risiko Metabolik Di Jakarta Selatan - Wijaya, Christian; Santoso, Alexander Halim; Destra, Edwin; Putra, Feri Yanto; Valdes, Angeline Florencia (Journal of Community Service and Society Empowerment, 2025)
Body mass index (BMI) and waist-to-hip ratio (WHR) are key indicators in evaluating metabolic risk. A high distribution of abdominal fat is closely associated with insulin resistance and various metabolic disorders. Mealtime-based interventions, such as time-restricted eating (TRE), are considered promising preventive strategies. This community education and anthropometric assessment were conducted at St. Francis of Assisi Church, South Jakarta, using the Plan–Do–Check–Act (PDCA) framework. Parameters evaluated included BMI and WHR, accompanied by visual educational materials on daily mealtime structuring. Among the 65 adult participants, the average BMI was 25.74 kg/m² and the average WHR was 0.9. A total of 56.92% were categorized as obese, and 83.08% exhibited a high WHR. These findings reflect a predominance of central adiposity, which is strongly associated with elevated metabolic risk. The high proportion of individuals with overweight and central fat accumulation highlights the urgency of preventive and promotive efforts. Educational interventions, particularly through poster-based delivery of information on time-restricted eating, present a feasible approach to raising public awareness on the importance of structured mealtimes as a preventive measure against metabolic disorders.